Structural transformations of economic functions of Warsaw - Przybyła, Katarzyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The purpose of the article is to identify the specialized (exogenous) functions ofPolish capital – Warsaw – and to analyze this town functional structure in the period 2004--2014. The discussed period is characterized by the development of country economy, whichcoincided with the Polish accession to the European Union structures. The conducted researchcovered the size, structure and changes of employment. The research was conducted at thebackground of economic base theory with regard to a city using two measures – surplusemployee index (SEI) and Florence’s index of specialization (FIS). The research can turn outuseful in urban development planning and in city management
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 476, s. 70-77
Keywords: city functions; methods for assessing functions of settlement units; funkcje miasta; metody oceny funkcji jednostek osadniczych